Pengaruh Efisiensi Modal Kerja, Likuiditas, dan Pengelolaan Piutang Usaha Terhadap Rentabilitas pada Perusahaan Sektor Industrial yang Terdaftar di BEI Periode 2022-2024 - Hilda Tria Mauliddyah; Hetty Muniroh (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the effect of working capital efficiency, liquidity, and accounts receivable management on profitability in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during 2022-2024. The research uses a quantitative methode with multiple linear regression analysis. The population consists of 63 industrial sector companies listed on the Indonesia Stock Exchange (IDX. The sampling technique used purposive sampling and obtained 16 companies as research samples with a total of 48 observations, which became observations after outlier data elimination. This research indicates that working capital efficiency and liquidity have a positive but insignificant effect on profitability, while accounts receivable management has a significant negative effect on profitability. This finding indicates that industrial sector companies have not fully optimized working capital efficiency and liquidity to increase profits, while accounts receivable management plays a more significant role in determining the fluctuations in the company’s profitability level. This research is expected to provide input and serve as a investors in assessing the performance of industrial sector companies listed on the Indonesia Stock Exchange (IDX).